HIV and obesity: updates in management strategies. Issue 2 (16th March 2023) - Parra-Rodriguez, Luis; O'Halloran, Jane A.
Abstract : Purpose of review: Weight gain has emerged as an important problem in people with HIV (PWH). When dealing with obesity, PWH face additional challenges to those without HIV. Understanding the nature of the problem and the modern evidence is essential to optimize management and identify knowledge gaps. Recent findings: Some PWH treated with antiretroviral therapy (ART) gain unhealthy amounts of weight and develop consequences of obesity. Newer agents have been consistently associated with excessive weight gain. Key studies are underway to inform the optimal use of specific ART in PWH dealing with obesity. For weight management, behavioral interventions fostering a healthier and active lifestyle, coupled with pharmacological therapies such as glucagon-like peptide 1 receptor agonists may be effective strategies in PWH, as recently demonstrated in those without HIV, although data in this regard is pending. Summary: A growing body of research has come to light in recent years regarding weight gain and obesity in PWH. However, much of the knowledge that inform current practices is extrapolated from studies in people without HIV. Modern ART regimens may promote excessive weight gain in some, and more research is needed to optimize ART selection and the use of weight loss medications.